Relationship between nursing students' global climate change awareness, climate change anxiety and sustainability attitudes in nursing: a descriptive and cross-sectional study - Nagihan İlaslan; Nuray Şahin Orak (BMC, 2024)
Abstract Background As a major global health threat, climate change is an important issue for nurses who play a pivotal role in health protection and improvement, and in the development of climate-smart healthcare systems. Sustainability attitudes in nursing should be developed together with awareness and concern for climate change. Aim The aim of this study was to determine the relationship between nursing students' global climate change awareness, climate change anxiety, and sustainability attitudes in nursing. Methods This descriptive, correlational study was conducted with 289 nursing students at a state university. Data were collected using the Descriptive Characteristics Form, the Global Climate Change Awareness Scale, the Climate Change Anxiety Scale, and the Sustainability Attitudes in Nursing Survey. Mean and percentage distributions, the Independent Samples t-test, ANOVA test, Pearson correlation and multiple regression analysis were used to analyze the data. The STROBE checklist was used to report this study. Results Global climate change awareness of the nursing students was at a moderate level, and the levels of climate change anxiety and sustainability attitudes in nursing were above average. There was determined to be a moderate positive correlation between climate change awareness and sustainability attitude in nursing, between anxiety and sustainability attitude in nursing, and between climate change awareness and anxiety. Climate change awareness and anxiety explained 25.1% of the sustainability attitude in nursing. Conclusions The study provides evidence of the relationship between nursing students' global climate change awareness and anxiety, and sustainability attitudes in nursing. It can be recommended that climate change and sustainability awareness-raising content are integrated into the nursing curriculum. The development of a sustainability attitude in nursing will contribute to the development of sustainable and low-carbon healthcare practices.